The heart failure and diabetes combo: higher risk, less care? - Schupp, Tobias; Akın, Ibrahim; Behnes, Michael (European journal of preventive cardiology, 2025)
Although the prognosis of patients with heart failure (HF) has steadily improved during the past decades, HF is still accompanied by mortality rates of up to 9% at 1 year and 30% at 2.5 years.1,2 In line with this, the prevalence of HF increases due to demographic changes and improved treatment strategies of patients with cardiovascular disease. HF patients nowadays typically present with a higher burden of cardiovascular and non-cardiovascular comorbidities,3 making the treatment of HF more complex during routine clinical practice. Even though current HF guidelines recommend the use of four pillars for the treatment of HF with reduced left ventricular ejection fraction (HFrEF),4 prescription rates of HF pharmacotherapies remain suboptimal, specifically in patients with comorbid type 2 diabetes mellitus (DM) or chronic kidney disease (CKD).5
Gesehen am 30.10.2025